Estimated pulmonary capillary wedge pressure assessed by speckle tracking echocardiography predicts successful ablation in paroxysmal atrial fibrillation. Issue 1 (December 2015) - Kawasaki, Masanori; Tanaka, Ryuhei; Miyake, Taiji; Matsuoka, Reiko; Kaneda, Mayumi; Minatoguchi, Shingo; Hirose, Takeshi; Ono, Koji; Nagaya, Maki; Sato, Hidemaro; Kawase, Yoshiaki; Tomita, Shinji; et al.
Abstract Background Atrial fibrillation (AF) is associated with left atrial (LA) remodeling caused by pressure and/or volume (LAV) overload. Increased pulmonary capillary wedge pressure (PCWP) represents LA pressure overload. We recently reported that pulmonary capillary wedge pressure (ePCWP) can be estimated by the kinetics-tracking (KT) index that combines LA function and volume using speckle tracking echocardiography (STE), and has a strong correlation with PCWP measured by right heart catheterization (r = 0.92). Therefore, we hypothesized that ePCWP is the best echocardiographic predictor of successful AF ablation. Methods We enrolled 137 patients with paroxysmal AF (age: 61 ± 10 years) who underwent pulmonary vein isolation. We measured LAV index, LA emptying function (EF) and LA stiffness during sinus rhythm before ablation using STE. PCWP was noninvasively estimated by STE as we previously reported. Parameters were compared between a group with AF recurrence (n = 30, age: 59 ± 11 years) and a group with successful ablation (sinus rhythm maintained for >1 year) (n = 107, age 61 ± 11 years). Results The ePCWP was correlated with PCWP measured by right heart catheterization (r = 0.76, p < 0.01). Compared with the non-recurrence group (n = 107, age: 61 ± 11), the AF recurrence group had significantly increased ePCWP (10.6 ± 3.5 vs 14.6 ± 2.9 mmHg, p < 0.01), minimum LAV index (29 ± 12 ml/m2 vs 37 ± 14 ml/m2, p < 0.01) and LA stiffness (0.47 ± 0.33 vs 0.83 ± 0.59, p < 0.01), but lower total LA EF (44 ± 11 % vs 39 ± 13 %, p < 0.01) before ablation. In multivariate logistic regression analysis, ePCWP was the most significant independent predictor of successful ablation. Using 13 mmHg of PCWP as the optimal cutoff value, the sensitivity and specificity for successful ablation were 73 and 77 % (area under the curve = 0.81), respectively. Conclusion The ePCWP that is measured by the combination of LA function and volume before ablation was a better predictor of the successful ablation compared with LA function and volume separately. The ePCWP estimated by STE is useful to predict the successful ablation in paroxysmal AF, and could be useful to improve candidate selection for AF ablation.